Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/s22239166
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for Slope Stability Classification of Circular Mode Failure: An Updated Database and Automated Machine Learning (AutoML) Approach

Abstract: Slope failures lead to large casualties and catastrophic societal and economic consequences, thus potentially threatening access to sustainable development. Slope stability assessment, offering potential long-term benefits for sustainable development, remains a challenge for the practitioner and researcher. In this study, for the first time, an automated machine learning (AutoML) approach was proposed for model development and slope stability assessments of circular mode failure. An updated database with 627 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Today, machine learning assists scientists in numerous fields of study [ 28 ]. Also, in medicine, scientific topics can be investigated using co-occurrence analysis, and their relationship can be gleaned directly from the subject content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Today, machine learning assists scientists in numerous fields of study [ 28 ]. Also, in medicine, scientific topics can be investigated using co-occurrence analysis, and their relationship can be gleaned directly from the subject content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schidler and Szeider [15] proposed the SAT-based decision tree method by combining heuristic and exact methods in a novel way, which successfully decreased the depth of the initial decision tree in almost all cases. Ma et al [16][17][18][19][20][21] adopted many well-established metaheuristics and the most recent metaheuristics to tune the hyperparameters of SVR and evaluated through nonparametric Friedman and post hoc Nemenyi tests to identify significant differences. Atalla et al [22] utilized machine learning and graphic analysis to design an automated intelligent recommendation system for academic consulting based on course analysis and performance modeling.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that GBM method is superior to RF, SVC and ANN in terms of accuracy, Kappa, F1 scores. Ma et al (2022) first developed an automated machine learning method (AutoML) to classify slope stability based on 627 cases of slope failure.…”
Section: Introductionmentioning
confidence: 99%
“…That means that a single machine learning algorithm performs unstable when facing different datasets and the generalization ability of that is not strong enough in evaluating slope stability (Zhang and Wang 2020). Moreover, slope cases of most database used in the above literature are small, which may lead to insufficient generalization ability of the model and need further verification of their applicability (Ma et al 2022). For example, when we obtain new slope cases for slope stability prediction, we cannot determine which algorithm is more suitable for evaluating slope stability because different literature provides different conclusions.…”
Section: Introductionmentioning
confidence: 99%